2014
DOI: 10.1371/journal.pone.0106337
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Paroxetine and Placebo in Treating Anxiety and Depression: A Meta-Analysis of Change on the Hamilton Rating Scales

Abstract: BackgroundPrevious meta-analyses of published and unpublished trials indicate that antidepressants provide modest benefits compared to placebo in the treatment of depression; some have argued that these benefits are not clinically significant. However, these meta-analyses were based only on trials submitted for the initial FDA approval of the medication and were limited to those aimed at treating depression. Here, for the first time, we assess the efficacy of a selective serotonin reuptake inhibitor (SSRI) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
31
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 48 publications
6
31
2
1
Order By: Relevance
“…While in line with older reviews in children 69 , this is in contrast to adult studies that found no significant differences in placebo effect size between depression and anxiety 70 . This contrast is not unique: placebo responses between children and adults differ significantly for binary outcomes across a wide variety of diseases 71 .…”
Section: Discussionsupporting
confidence: 77%
“…While in line with older reviews in children 69 , this is in contrast to adult studies that found no significant differences in placebo effect size between depression and anxiety 70 . This contrast is not unique: placebo responses between children and adults differ significantly for binary outcomes across a wide variety of diseases 71 .…”
Section: Discussionsupporting
confidence: 77%
“…Antidepressants are also commonly used for anxiety disorders, OCD, and PTSD (Wong et al., ), but comparatively little evidence regarding the influence of severity is available for these disorders. Trial‐level meta‐analyses have found no evidence that antidepressant efficacy increases with increasing severity (Ackerman & Greenland, ; Curtiss, Andrews, Davis, Smits, & Hofmann, ; Davis, Smits, & Hofmann, ; de Vries, de Jonge, van den Heuvel, Turner, & Roest, ; Sugarman, Loree, Baltes, Grekin, & Kirsch, ). However, such trial‐level analyses may be prone to the ecological fallacy (Thompson & Higgins, ), in which a trial‐level relationship can be found that does not exist at the participant level, or vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, haloperidol was the most common typical antipsychotic to which atypical antipsychotics were compared (Leucht, Kissling, & Davis,, 2009). In the realm of anxiety treatment, publication bias has been demonstrated for paroxetine (Sugarman, Loree, Baltes, Grekin, & Kirsch, 2014). Further, haloperidol was often given in unnecessarily high doses, leading to increased adverse events and likely reduced efficacy, making the atypical antipsychotics appear safer and a bit more efficacious in comparison (Leucht et al, 2009).…”
mentioning
confidence: 99%